Abuse of Process in Extreme Grace Period Clauses in Debt Suspension Settlements - David, Norman (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the legal construction of extreme grace period clauses in Suspension of Debt Payment Obligations (PKPU) settlement proposals and to assess whether such clauses constitute abuse of process despite formal procedural compliance. Using doctrinal legal research with statutory and conceptual approaches, this study examines Law Number 37 of 2004 and develops a normative framework based on proportionality, good faith, and creditor protection through qualitative interpretive analysis. The findings reveal a critical normative gap in Indonesian insolvency law, namely the absence of clear parameters governing the reasonableness of grace periods, which enables debtors to strategically design excessively long and selectively applied deferral clauses that disproportionately burden non-dominant creditors. Although formally validated through the PKPU voting mechanism and homologation process, such clauses undermine the substantive objective of PKPU as a balanced collective restructuring instrument by eroding the economic value of creditor claims. This study establishes that extreme grace period clauses may be classified as a structural form of abuse of process when they exploit procedural legitimacy to achieve substantively unjust outcomes. The novelty of this research lies in conceptualizing extreme grace period clauses as a distinct doctrinal category within the abuse of process framework in Indonesian bankruptcy law, as well as in developing operational indicators—proportionality, non-discrimination, and compensatory mechanisms—for assessing their legality. The study contributes theoretically by advancing a shift from procedural legality to substantive justice in insolvency law, and practically by proposing proportionality-based judicial review and regulatory reform to strengthen creditor protection and ensure the integrity of the PKPU mechanism.
Keywords: Abuse of Process; Creditor Protection; Good Faith; Grace Period Clause